DESIGNING ELDERLY-FRIENDLY PUSKESMAS FACILITIES USING AGE-FRIENDLY PRINCIPLES (CASE STUDY PUSKESMAS X) - Bambang Suhardi; Farhana Mazaya Putri1; Rahmaniyah Dwi Astuti; Ervina Rahmi Hawa (Malaysian Journal of Public Health Medicine, 2024)
According to the 2019 World Population Prospects, globally, the proportion of older people is projected to increase to 16% by 2050 so that by 2050, 1 in 6 people in the world will be over 65 years old. WHO recognizes the important role of primary healthcare centers to be accessible and adapted to the needs of the elderly population. Puskesmas X is one of the health centers in Karanganyar, Central Java. This health center has encouraged efforts to improve health services for the elderly by creating a special clinic for the elderly. However, several aspects of elderly-friendly health services still have not been fulfilled. This study was conducted to identify and evaluate the suitability of health center design in terms of age-friendly principles and regulations related to the provision of elderly health services at health centers and provide recommendations for improving the design of health center facilities by taking into account the human side (ergonomics). The evaluation of elderly-friendly principles in health centers was carried out based on a checklist developed from the WHO toolkit and Indonesian laws and regulations. Based on the checklist that was developed, Puskesmas X received a score of 70% or in the yellow achievement category as a health center that fulfills the principle of being friendly to the elderly. Proposed improvements to the facilities provided for Health Centre X are improvements for the elderly services procedures, parking lots, corridors, signage, waiting chairs, elderly polyclinics waiting room layouts, elderly medical bed, pharmacy counter, pharmacy counter waiting room layouts, and toilets.